Educational Benefits of Cu An Kiong Lasem Temple in Social Science Learning - Alifatur Rizqi Nur Awwaliyah; Yusuf Falaq (STKIP Taman Siswa Bima, 2023)
Cu An Kiong Lasem Temple is one of the oldest temples in Lasem, located around the Babagan river. This sincerity has a continuous history of Chinese civilization which until now can still be found some ancient relics of former glory. This aim of article is to analyze the educational benefits of Cu An Kiong Temple in Lasem as an educational resource within the context of Social Studies at SMA N 1 Lasem. Cu An Kiong Temple is likely a significant historical and cultural site that plays a vital role in the study of this subject. This article will explore how Cu An Kiong Temple contributes to students' understanding of Chinese history, culture, and traditions, with a focus on the local context of Lasem. The article will also discuss approaches and teaching strategies that teachers can employ to integrate Cu An Kiong Temple into the Social Studies curriculum. This may involve field trips, research projects, or experiential learning methods to engage students and enhance their comprehension of the subject matter. Supported by research or case studies, this article will emphasize that Cu An Kiong Temple is not merely a tourist attraction or historical site but also an effective tool to enrich students' learning experiences in Social Studies and promote a better understanding of Chinese culture and history in the local environment.